Multifunctional all-in-one adhesive hydrogel for the treatment of perianal infectious wounds - Yin, Ge; Wang, Jingyue; Wang, Xiao; Zhan, Yu; Tang, Xuegui; Wu, Qie; Wang, Xian; Du, Lijuan; Lu, Xiong (Frontiers in Bioengineering and Biotechnology, 2022)
Postoperative wound of perianal infectious disease represents a common but unique refractory wound in clinical practice. The reasons that hinder the wound healing process include not only the severe bacterial infection of the wound itself and the narrow and deep shape of the wound, but also its frequent bacterial contact. Therefore, the development of biofunctional dressings to aid in therapy is essential. In this study, we synthesized a new type of dressing comprising a hydrogel host based on the Schiff base principle and catechol groups between polydopamine, oxidized dextran, and quaternized chitosan, and then loaded it with traditional Chinese medicine molecules. These formed an integrated hydrogel for accelerated wound repair in a perianal infection model. The prepared hydrogels exhibited excellent wet tissue adhesion, antifouling, morphological variability, suitable swelling properties, and complete degradability, as well as remarkable contact antibacterial ability and the ability to rapidly scavenge free radicals. Hemostatic experiments showed excellent hemostatic properties, as the integrated hydrogel could instantly gel to seal the hemorrhage. Hemocompatibility and in vitro cell experiments showed that the integrated hydrogel had good biosafety and significantly promoted cell proliferation, which in turn accelerated the repair of infected whole cortexes in rats. A histomorphological evaluation showed that the integrated hydrogel promoted the recovery of normal anatomical tissue in rats by promoting the formation of collagen fibers and inhibiting inflammation. The results showed that this multifunctional integrated hydrogel has great potential for the treatment of continuously infected skin regeneration, providing a promising therapeutic strategy for postoperative wound healing in perianal infectious diseases.